Critical factors that influence the success of implementing value management in Malaysian construction industry - 401024 Chua, Tee Khoon @ Chua Yong Peng; Chua, Yong Peng (Skudai : Universiti Teknologi Malaysia, 2004)
Thesis (Master of Science (Construction Management)) - Universiti Teknologi Malaysia, 2004